Collagenase Production by Nematode-Trapping Fungi - Schenck, Susan (1980)
A number of species of nematode-trapping fungi, which capture and digest nematodes having keratin and collagen in their cuticles, were tested for the ability to produce extracellular collagenase and keratinase. Collagenase, which is active on ichthyocol, earthworm collagen, and procollagen from chicken embryo fibroblasts, was found in the growth medium of all tested species; keratinase was not found. The enzyme from Arthrobotrys amerospora was concentrated by precipitation with (NH(4))(2)SO(4) and further purified by adsorption on collagen at 0°C. The collagenase was active over a pH range of 2.5 to 10.0. It was not inactivated by dialysis against ethylenediaminetetraacetic acid for 48 h or by the sulfhydryl group inhibitors N-ethylmaleimide and p-chloromercuribenzoate. The production of collagenase may aid the fungus to penetrate the cuticle of its prey.